2007
DOI: 10.1177/1049732307301335
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Antiretroviral Access and Adherence in Mexico

Abstract: The goal in this article is to examine social problems associated with highly active antiretroviral therapy (HAART) adherence in Mexico and the related challenges for Mexican persons living with HIV/AIDS (PLWHAs). The study was conducted from the perspective of infected and affected individuals. The authors completed 64 in-depth interviews with heterosexual male and female PLWHAs, as well as with some key individuals from their social network. Following the principles of grounded theory, they carried out induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
1
28
1
2
Order By: Relevance
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 30 studies, 21 were from Africa,* 6 from east/southeast Asia,The data collection methods described in the papers comprised mostly of interviews (22 studies), y surveys (7 studies), 16,27,29,34,39,40,42 review of clinical data (7 studies), 18,20,22,27,31,36,38 and focus-group discussions (6 studies). 21,23,28,32,42,43 Respondents included PLWHA with/without ART (22 studies), z noninfected people including elders, teenagers, and university students (11 studies), § health care workers including nurses, doctors, social workers, laboratory technologists (7 studies), 15,21,25,28,30,42,43 family members and/or friends of PLWHA (5 studies), 17,19,21,25,43 traditional healers (1 study), 21 and representatives of nongovernmental and community-based organizations (NGOs and CBOs; 1 study).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations